2019
DOI: 10.3928/23258160-20190605-03
|View full text |Cite
|
Sign up to set email alerts
|

Association of Retinal Inner Layer Disorganization With Ultra-Widefield Fluorescein Angiographic Features and Visual Acuity in Branch Retinal Vein Occlusion

Abstract: BACKGROUND AND OBJECTIVE: To assess the impact of the disorganization of retinal inner layers (DRIL) on visual acuity (VA) and its correlation with ischemic index (IsI) on ultra-widefield fluorescein angiography (UWFFA) in eyes with acute, treatment-naïve branch retinal vein occlusion (BRVO). PATIENTS AND METHODS: Retrospective, longitudinal study of BRVO eyes with 1 year of follow-up or more. Area of intraretinal cysts, DRIL length, extent of disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Rayess et al showed that a higher initial subfoveal choroidal thickness was a positive predictor of favorable visual outcomes in patients with BRVO by univariate analysis but not multivariate analysis ( 68 ). In contrast Yu et al ( 69 ) reported that choroidal thickness did not impact VA at any time point in patients with BRVO. However, another study examined in detail the choroidal change of RVO ( 70 ).…”
Section: Optical Coherence Tomographymentioning
confidence: 83%
“…Rayess et al showed that a higher initial subfoveal choroidal thickness was a positive predictor of favorable visual outcomes in patients with BRVO by univariate analysis but not multivariate analysis ( 68 ). In contrast Yu et al ( 69 ) reported that choroidal thickness did not impact VA at any time point in patients with BRVO. However, another study examined in detail the choroidal change of RVO ( 70 ).…”
Section: Optical Coherence Tomographymentioning
confidence: 83%
“…[16,17] Previous studies have noted that vision recovery was limited even though retinal thickness was reduced to normal levels after treatment. [18,19] The reason for this is not clear. It is known that macular edema was noted mostly in the outer nuclear layer, causing photoreceptor cell loss and fovea dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that macular edema was noted mostly in the outer nuclear layer, causing photoreceptor cell loss and fovea dysfunction. [19] Akagi-Kurashige et al found that macular photoreceptor abnormalities of RVO patients could cause a decrease in parafoveal cone density and disrupt the cone mosaic spatial arrangement. [20] Therefore, the assessment of the retinal layers, especially those consisting of photoreceptor layers, is useful for evaluating visual prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted that vision recovery was limited even though retinal thickness was reduced to normal levels after treatment [ 22 , 23 ]. The reason for this is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is not clear. It is known that macular edema was noted mostly in the outer nuclear layer, causing photoreceptor cell loss and fovea dysfunction [ 23 ]. Akagi-Kurashige et al found that macular photoreceptor abnormalities of RVO patients could cause a decrease in parafoveal cone density and disrupt the cone mosaic spatial arrangement [ 24 ].…”
Section: Discussionmentioning
confidence: 99%